Temporal lobe epilepsy: origin and significance of simple and complex auras. - Taylor, D C (1987)
The aura experience of 88 patients with temporal lobe epilepsy was recorded, classified and analysed. Despite the great richness of the 215 experiences described, correlations with left or right brain, nature of lesion, age of onset, etc. were only apparent when a classification into three aura groups was used. "Simple primitive" auras as sole auras were more likely with early onset epilepsy, in lower IQ patients, in males, from the right temporal lobe, and with mesial temporal sclerosis. Exclusively "intellectual" auras were confined to a group of high IQ males. The number of aura experiences described per person correlated with Verbal IQ for males but not females, but also varied with side, sex, and nature of lesion. The results are discussed in terms of the necessary conditions for aura and their relevance and in relationship to the results of brain stimulation studies by Penfield and others.